Analisis Semantik Mimesis dalam Bahasa Jepang pada Anime Jujutsu Kaisen: Representasi dan Makna - Yismaya Suprihastiadi; Melinda Dirgandini (Program Studi Sastra Jepang, Fakultas Ilmu Budaya, Universitas Udayana, 2025)
Onomatopoeia is an imitation of sounds in the form of words to describe the state or sound produced by living things and inanimate objects. Onomatopoeia and mimesis have the same meaning, namely imitating or imitating sounds. In anime, mimesis is used to describe the state or activity of living things and inanimate objects. This study aims to describe the use of mimesis, types of mimesis, and the meaning of Japanese mimesis in the anime 呪術廻戦Jujutsu Kaisen. This study uses a qualitative descriptive method with literature study research techniques. The results of the study show that mimesis is widely used to clarify the expression of characters and the atmosphere of the story. The most dominant type of mimesis is giyougo, which describes the state or activities of a character. In addition, it was found that the meaning of mimesis can change depending on the context of its use in dialogue. This study provides a deeper insight into the role of mimesis in Japanese communication, particularly in popular media such as anime.